Different Types of Early Life Stress Affected Histone H4 Acetylation in the Left Prefrontal Cortex of Mice in Different Pathways - Maulana Ikhsan (Faculty of Medicine University of Malikussaleh, 2024)
Histone H4 acetylation is an epigenetic change that regulates gene expression and is linked to a variety of neurological functions. The purpose of this study was to see how different types of early life stress affected histone H4 acetylation in the left prefrontal cortex (PFC) of mice. Histone acetylation levels were determined using Western blot analysis in four groups: control, control isolation, chronic stress, and chronic unpredictable stress. The control group comprised of mice that were not disturbed from birth until weaning, whereas the control isolation group was isolated after weaning. The chronic stress group was separated from their mothers on a daily basis, whereas the chronic unpredictable stress group was separated from their mothers on specified weekdays. Stress, according to our findings, may raise histone modification levels, whereas routine and repetitive stress situations may produce habituation behavior as a compensatory mechanism. Notably, this study provides preliminary evidence that different types of stress alter H4 acetylation in the PFC in mice. Understanding the molecular mechanisms governing histone acetylation in response to early life stress can offer light on the neurobiological processes at work and help to create tailored therapies for stress-related illnesses.